2020
DOI: 10.3390/su12052132
|View full text |Cite
|
Sign up to set email alerts
|

Management Accounting Systems, Top Management Teams, and Sustainable Knowledge Acquisition: Effects on Performance

Abstract: Organizations are increasingly aware of the importance of managing the acquisition processes of new and sustainable knowledge, which allows them to increase performance. These knowledge-acquisition processes require top management teams to focus on the external environment to search for sustainable opportunities and initiatives. This spurs top teams to make strategic decisions that require more comprehensive managerial information, which is provided by management accounting systems. Our research analyzes how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The decision on whether a firm will conduct green innovation lies with its executives. The greater the heterogeneity of an executive's professional background, the richer their level of expertise and skills (Ugalde Vásquez & Naranjo‐Gil, 2020). This feature makes firms more aware of green risks and the government's market environment.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The decision on whether a firm will conduct green innovation lies with its executives. The greater the heterogeneity of an executive's professional background, the richer their level of expertise and skills (Ugalde Vásquez & Naranjo‐Gil, 2020). This feature makes firms more aware of green risks and the government's market environment.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…It enables the organization to improve its performance as organizations can achieve sustainability by acquiring new competencies and transferring them across various organizational levels. Consequently, organizations have not only to care about how to gain knowledge but also efficiently manage the knowledge acquisition process to achieve knowledge strategy [9,26]. Al Yami et al [27] highlighted that the acquired knowledge should be codified and preserved so that it may be included in the organization's current knowledge base, as technological advances allow organizations to codify, digitalize, and automate processes quickly.…”
Section: Knowledge Acquisitionmentioning
confidence: 99%
“…FIs use knowledge management solutions to share data across the organization, allow authorized access to sensitive information, block unauthorized access and analyze potential investments. Ugalde Vasquez and Naranjo-Gil (2020) revealed that knowledge management acquisition affects the management accounting systems and impacts the application of management accounting practices.…”
Section: Literature Reviewmentioning
confidence: 99%